Nursing Care for Sensory Perception Disorders in Elderly Patients with Auditory Hallucinations at Iryou Houjin Aiwakai (Ikeda En) Aiwa Deikea Room Okinawa Japan - Siti Fatimah; Ita Apriliyani; Ririn Isma Sundari (LPPM Universitas Harapan Bangsa, 2024)
Japan has the world's largest elderly population, with a family culture that entrusts elderly care to nursing homes, or the so-called Roujin Home. In 2020, there were around 11,575 Roujin Houses in Japan. A common problem that arises in patients with auditory hallucinations is sensory perception disorders. The purpose of this study is to reveal the impact of therapy or reprimands in the healing process of auditory hallucinations in elderly patients. This research was conducted on June 20-22, 2023 at Iryou Houjin Aiwa Deikea, using observation instruments and interviews with patients and therapists. The study focused on one patient with auditory hallucinations. The results showed that the intervention given for 3 days did not provide significant progress, due to a lack of support and motivation from the family, which caused the patient to be reluctant to follow the reprimanding therapy. Limitations of this study include limited duration of intervention and lack of emotion supports from the family. These findings provide important insights into the importance of family support in improve the effectiveness of auditory hallucination therapy.